Evil dead rise [videorecording (Blu-Ray + DVD)] - Cronin, Lee, 1982-; Cronin, Lee, 1982-; Sutherland, Alyssa, 1982-; Sullivan, Lily; Echols, Gabrielle; Davies, Morgan; Fisher, Nell, 2011-; McKeon, Stephen (Warner Bros. Entertainment, 2023)
Moving the action out of the woods and into the city it tells a twisted tale of two estranged sisters, played by Sutherland and Sullivan, whose reunion is cut short by the rise of flesh-possessing demons, thrusting them into a primal battle for survival as they face the most nightmarish version of family imaginable.